Response of Two Sesame (Sesamum indicum L.) Cultivars to Nitrogen and Phosphorus Fertilization under Rain Fed Conditions - Ahmed, Ahmed Mohamed Mohamed; Hago, Tageldin El Sheikh Musa (University of Khartoum Journal of Agricultural Sciences, 2023)
A field experiment was conducted for two consecutive seasons (2002/2003 and 2003/2004) in the Experimental Farm of the Faculty of Agriculture, University of Sinnar, Abu Naama, Sudan. The objective was to study the response of two sesame (Sesamum indicum L.) cultivars to nitrogen and phosphorus fertilization under rain fed conditions. The treatments were four nitrogen levels (0, 40, 80, 120 kgN/ha) and four phosphorus levels (0, 50, 100, 150 kgP 2 O5 /ha). Urea (46% N) and triplesuperphosphate (48% P 2 O5 ) were used as sources of nitrogen and phosphorus, respectively. Two improved sesame cultivars, Khidir and Promo, were used in the study. The experiment was laid out in a split-split plot design with four replicates. Nitrogen treatments were assigned to the main plots, whereas cultivars and phosphorus treatments were allotted to the sub and sub-sub plots, respectively. The results showed that both nitrogen and phosphorus had significant effects on plant height, shoot dry weight, height to the first capsule, capsule number/plant, percentages of capsules on the main stem and the branches and seed yield. The cultivars showed significant differences in some growth and yield attributes, with Promo exhibiting better growth and giving higher yield than Khidir. There was significant interaction between cultivars and nitrogen on seed yield in both seasons